Pengaruh E-security, E-service Quality terhadap E-satisfaction dan Pengaruh E-satisfaction, E-security, dan E-service Quality terhadap E-repurchase Intention Secara Langsung pada Pengguna E-commerce Tokopedia - Gosal, Go Brian R.; Bernarto, Innocentius (JURNAL ADMINISTRASI BISNIS (JAB), 2021)
The purpose of the study is to determine: 1) Weather E-security from E-commerce Tokopedia has a positive effect on E-satisfaction. 2) Weather E-service quality from e-commerce Tokopedia has a positive effect on E-satisfaction. 3) Weather E-satisfaction from e-commerce Tokopedia has a positive effect on E-repurchase intention. 4) Weather E-security from e-commerce Tokopedia has a positive effect on E-repurchase intention. 5) Weather E-service quality from e-commerce Tokopedia has a positive effect on E-repurchase intention. This research was conducted in the Jabodetabek area. With a quantitative type of research using 200 respondents. The data collection method in this study was a questionnaire survey, conducted by using Google form, with a non-probability sampling. Data analyzed method using SmartPLS software. The results of the concluded study are E-security and E-service quality affect E-satisfaction positively and significantly, then E-satisfaction, E-security, and E-service quality affect E-repurchase intention positively and significantly.